Timing of recurrence after treatment of pulmonary TB - C.T. Mithunage; D.W. Denning (IJTLD Open)
Pulmonary TB (PTB) may recur due to reinfection or relapse after initial successful treatment. Based on microbiologically documented cases, we searched Embase, PubMed, Web of Science, and Medline for PTB recurrence. The timeframe of overall recurrences, relapse, reinfection, and risk factors were assessed. We compared the time to recurrence, relapse, and reinfection from treatment completion and plotted this using Kaplan–Meier curves. This systematic review included 23 articles describing 2,153 PTB recurrences in 75,224 treated people across all continents. Genotyping data to distinguish relapse from reinfection was available for 402 recurrences. The cumulative recurrence percentage was 2.9% over 5 years, and the median time for recurrence was 18 months (95% CI 16.99–19.0). Most recurrences (93%) were in HIV-negative people. Relapse occurred earlier than reinfection at 12 months (95% CI 10.86–13.14) vs 24 months (95% CI 21.61–26.39) (P < 0.001, χ2 59.89). In low TB burden settings, recurrences were mainly caused by relapse (85%), whereas in high-burden settings, relapses comprised 56% of recurrences. Recurrences occurred slightly earlier in HIV-positive patients (P = 0.038, χ2 4.30). The emergence of resistance to one or more first-line anti-TB agents was documented in 40 of 421 cases (9.5%). Early recurrences are mainly relapses, while late recurrences are mainly reinfections.